The role of quality characteristics in pricing hard red winter wheat. (April 2022) - Roberts, Shane; Brooks, Kathleen; Nogueira, Lia; Walters, Cory G.
Highlights: Conventional and end-use quality characteristics have an important effect on the price of U.S. HRWW. Producers are paid indirectly through regional HRWW prices. Prices are updated as harvest progresses to reflect changes in wheat quality. The market quality information available to wheat industry participants can influence price. Revisions to U.S. policy on standard grade factors to improve transparency. Abstract: This study empirically examines the role of conventional and end-use wheat quality characteristics as well as transportation costs on the pricing of U.S. hard red winter wheat (HRWW) utilizing a hedonic price analysis framework, detailed quality characteristic data as well as location matched price data. We find evidence that multiple conventional quality characteristics and multiple end-use quality characteristics (milling and baking) have a statistically significant and economically important effect on the price of U.S. HRWW. This evidence suggests that, although U.S. HRWW producers are not directly paid premiums or discounts for end-use quality characteristics, they can be paid indirectly through regional HRWW prices. We also evaluate the role of information about conventional and end-use quality characteristics on price as harvest progresses. Results suggest that as harvest progresses, prices are updated to reflect changes in wheat quality. Results suggest revisions to U.S. policy on standard grade factors to improve transparency between characteristics farmers are paid for on grade sheets and characteristics millers and bakers value.